Analisis Faktor- Faktor Lion Air Sebagai Maskapai Dengan Pangsa Pasar Terbesar Di Tahun 2021 - Merna Devilia Gerda Mnuro; Amelia Puspa Tamara (Universitas Sains dan Teknologi Komputer, 2023)
Lion air group is an airline that implements the Low Cost Carrier (LCC) strategy which occupies the largest share of the domestic aviation market in Indonesia in 2021 during the co-19 pandemic. The contribution of Lion Air airlines in achieving its target continues to increase so that in this case this research was carried out to find out how Lion Air maintains it. This research uses the literature study method and was carried out from May to June 2023 in Yogyakarta by collecting library data by reading and recording all the important main ideas contained in previous research journal data that have been tested and trusted websites which are then processed as research material. The results of this study are that there are three important factors that underlie Lion Air's success in occupying market share, namely price, flight routes that have many choices and efficiency and a large number of fleets. Of the three factors, price is the most important factor because Lion Air is able to provide the service that its customers want, namely low prices. Lion Air knows that the majority of people have a tendency to choose cheap goods, so this is an opportunity for Lion Air to maintain market share.